Exercise capacity is associated with rest and peak-exercise left ventricular global longitudinal strain in patients with hypertrophic cardiomyopathy. (25th November 2020) - Fava, A.M; Alashi, A; Saijo, Y; Sande Mathias, I; Popovic, Z; Thamilarasan, M; Lever, H; Desai, M.Y
Abstract: Background: Patients with hypertrophic cardiomyopathy (HCM) frequently have reduced exercise capacity, which can be associated with subclinical cardiac dysfunction. Left ventricle global myocardial strain (LV-GLS) is a sensitive index to detect subclinical myocardial dysfunction. However, the clinical utility of LV-GLS during exercise test remains uncertain. Purpose: We assessed the association of functional capacity with LV-GLS at rest and at the peak of stress in HCM patients. Methods: We examined 566 asymptomatic/minimally symptomatic HCM patients (54±14 years, 57% men, body mass index 30±6 kg/m 2, 84% on beta-blockers) by echo at rest and following maximal exercise. We recorded clinical, echo variables (LV ejection fraction [LVEF], LV thickness, left ventricle mass index [LVMI], left ventricle outflow tract [LVOT] gradient, LV-GLS at rest and at peak stress), and exercise variables (percent of age-gender predicted metabolic equivalents [AGP-METs]). Results: Echo parameters were as follows: LVEF at rest of 62±6%, wall thickness of 16.9±0.4 mm, LVMI of 117±47 g/m 2, LVOT gradient at rest of 27±33 mmHg, LV-GLS at rest of −15.9±3.6%, LV-GLS at peak of stress of −17.4±4.3%, and change in LV strain from rest to stress of −1.9±2.3%. Only 41% of patients achieved >85% of AGP-METs. Logistic regression demonstrating an association between AGP-METs less than 85% and various predictors are shown in Table 1. Conclusion: Impaired deformation at peak of stress assessed by LV-GLS was associated with reduced exercise capacity measured as AGP-METs less than 85%. These findings suggest that early systolic cardiac deterioration should be considered as a cause of exercise impairment in patients with HCM. Funding Acknowledgement: Type of funding source: None